2003
DOI: 10.1046/j.1365-2621.2003.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage under a modified atmosphere on the microbiological and organoleptic qualities of ground beef prepared from pasteurized manufacturing beef

Abstract: Summary A 40‐kg lot of manufacturing beef, i.e. meat used for the production of ground beef products, was collected at a beef packing plant. The lot was divided into two batches. One batch was pasteurized by immersion in water at 85 °C for 60 s, the other batch was not pasteurized. Both batches were then ground. The ground meat was packed in overwrapped trays, which were master packaged under a modified atmosphere of 70% O2 : 30% CO2. The master packs were stored at 2 °C for up to 12 days. At the time of pack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This type of an effect had previously been reported on red meats previously (2, 9, 18) and on ground beef (8,17). The samples from the C group had relatively high increases in their specific counts of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This type of an effect had previously been reported on red meats previously (2, 9, 18) and on ground beef (8,17). The samples from the C group had relatively high increases in their specific counts of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 80%
“…was noticed. This type of suppression on the growth of pseudomonads was previously linked to the inhibitory effect of CO 2 levels at or above 20% used in MAP by several authors (6,8). The reduction and/or stalling of B. thermosphacta at constant numbers during MAP conditions in our study is concordant with the findings of Tremonte et al (19), and discordant with the results of Tsigarida et al (20), Skandamis and Nychas (17,18), who reported increases in the numbers of this bacterium in their studies.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Modified-atmosphere-packed foods have become more available to meet consumer demand for fresh, refrigerated foods with extended shelf lives, being used to increase the shelf-life of fresh meat, poultry and fish products, among others (Chouliara et al, 2008;Gill and Badoni, 2003;Rosnes et al, 2006). The principle of MAP is the replacement of packaged air with a different, fixed gas mixture.…”
Section: Introductionmentioning
confidence: 99%